Transient musical hallucinosis of central origin: a review and clinical study. Issue 11 (November 1992) - Paquier, P; van Vugt, P; Bal, P; Cras, P; Parizel, P M; van Haesendonck, J; Creten, W; Martin, J J
Abstract : A 52 year old, right handed, hearing impaired woman was admitted with headache and neck stiffness. The only neuropsychological symptom was transient auditory perceptions in the left ear, which were musical, seemed familiar and were not influenced by verbal communication. CT and MRI showed a right subarachnoid haemorrhage, while brainstem auditory evoked potentials failed to reveal a brainstem lesion. In patients with organic cerebral disease, unilateral auditory hallucinations (AHs) may indicate a lesion in the contralateral hemisphere. However, according to this review the type of AHs (verbal versus musical) is not consistently associated with a cerebral lesion on either side.